Proses dan Hasil Belajar Mengunakan Model Problem Based learning pada Pembelajaran Pendidikan Pancasila - Firdaus, Ahmad; Abdulah; Aldino (CV. Master Literasi Indonesia, 2025)
The low learning outcomes of students in Pancasila Education. This situation demands learning innovation through the application of the Problem-Based Learning (PBL) model. The purpose of this study was to determine the effectiveness of the Problem-Based Learning model in improving student learning processes and outcomes in Pancasila Education, as well as to examine its implications and impact on active engagement and critical thinking skills. This study was a classroom action research (CAR) conducted in two cycles. The subjects were 20 sixth-grade students of SDN 104/II Sungai Pinang in the odd semester of the 2025/2026 academic year. Each cycle consisted of planning, action implementation, observation, and reflection. The results showed that the application of the Problem-Based Learning model improved student learning processes and outcomes. Improvements were evident in the learning process, with the average achievement score increasing from 70% in cycle I to 79.5% in cycle II. Meanwhile, learning outcomes also experienced significant improvements. For analytical skills, scores increased from 35% to 80%; Synthesis skills increased from 45% to 75%; problem-recognition and problem-solving skills increased from 40% to 80%; and conclusion skills increased from 50% to 70%. The implications of implementing the Problem-Based Learning model not only improve academic outcomes but also foster critical thinking, collaboration, and student responsibility for learning. Furthermore, this model encourages teachers to be more creative in designing student-centered learning, thus making Pancasila Education more contextual, meaningful, and fostering a reflective attitude toward Pancasila values.